Study on Corrosion Resistance and Welding Properties of High Strength, Tough Bainite Steel CB10 - Cheng, Xiao-Le; Zhou, Si-Jun; Xu, Guang-Shen; Fu, Han-Guang; Bai, Bing-Zhe (Frontiers in Materials, 2019)
In order to achieve high strength and toughness in bainite steel, the authors carried out a study on their self-developed CB10 steel. The CB10 steel was heat-treated at different tempering temperatures to control its microstructure and mechanical capabilities, and, further, changes in its structure were explored. The results showed that bainite, ferrite, and M/A islands could be engendered when CB10 steel was tempered at 250°C, 450°C, 600°C, and 670°C, respectively. With an increase in tempering temperature, lath-type bainite began to merge and coarsen obviously, and polygonal ferrite appeared. When the tempering temperature was above 600°C, recovery and recrystallization occurred in some regions. In particular, the mechanical properties of CB10 steel were best at a 450°C tempering temperature; among them, its tensile strength was 632 MPa, its yield strength was 487 MPa, elongation was 25%, and the Charpy absorbed energy was >140 J. Furthermore, the anti-hydrogen-induced cracking performance and weldability of CB10 steel were tested. The results indicated that there were no cracks on the surface of the sample, indicating that it has excellent anti-hydrogen-induced cracking performance and weldability. Moreover, the maximum hardness of the heat-affected zone was 231 Hv, the maximum Charpy absorbed energy was 285.0 J, and the fracture morphology was in all cases ductile fracture when the impact temperature was above −60°C.